(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2016)
The teaching-learning process of concepts allows for the establishment of the necessary theoretical and methodological foundations to guide the comprehensive development of schoolchildren, an aspect that has been addressed from various perspectives by internationally and nationally renowned authors, whose research provides the theoretical and methodological foundations to be taken into account by teachers in guiding this process, as well as in the psycho-pedagogical diagnosis and intervention that is carried out in Cuban schools today.